A GENRE-BASED DISCOURSE ANALYSIS: CHRISTMAS INVITATION LETTER IN GKPS INDONESIA - Karima, Annisa; Saragih, Frans Dhaniko Cristian; Priyatama, Muhammad Rangga; Simorangkir, Nico Sahpudan; Zein, T. Thyrhaya (SIGEH ELT : Journal of Literature and Linguistics, 2025)
This study examines the genre-based discourse of Christmas invitation letters within the Simalungun Christian Church (GKPS) in Indonesia. Using Swales' (1990) genre move analysis and the multimodal approach of Kress and Van LeeuwenÂ (1996), the study identifies six key moves present in the structure of the invitations: opening, congratulating the recipient, stating the purpose and message, providing event details, making formal requests, and concluding with official signatures. These moves highlight how the invitations not only communicate event information but also reflect Christian religious values and Indonesian cultural norms. The analysis underscores the importance of language and visual elements in conveying social and religiousÂ unity within the community. This research contributes to a broader understanding of how genre functions within religious and cultural contexts